Extracurricular Implementation of Islamic Education in Character Building Students in MTs EX PGA UNIVA Medan - Siti Fatimah Siregar; Mardianto Mardianto; Akmal Walad Ahkas (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
Education in Indonesia in the last decade has reaped many problems including the weak character of the young generation where the success of a nation can be seen from the character of the younger generation. Seeing these problems, there needs to be some breakthroughs, one of which can be done through character inculcation that is applied in schools through classroom learning and other activities such as extracurricular activities. This research method is qualitative with the type of descriptive research, namely the type of research that examines data that can describe complex and concrete social realities. This study uses data collection techniques such as observation, interviews, library methods and the use of documentation. The analysis in this study uses interactive data analysis from Lexy Moleong with the pre-field stage, the implementation stage, the data analysis stage, the conclusion stage and the reporting stage. The results showed that: (1) the implementation of extracurricular Islamic Religious Education in MTs EX PGA UNIVA Medan there were 13 extracurricular Islamic Religious Education. (2) extracurricular activities in MTs EX PGA UNIVA Medan are essentially many activities. However, in this discussion, only PAI extracurricular activities were taken which presumably had a stake in the formation of student character, for example the types of PAI extracurricular activities namely introduction of the holy book, worship, social activities, habituation of noble character and the inculcation of religious historical values. Through this activity students can learn to develop communication skills, collaborate with others, discipline and other characters.